Association of long-term aspirin use with kidney disease progression - Lu, Jun Ling; Shrestha, Prabin; Streja, Elani; Kalantar-Zadeh, Kamyar; Kovesdy, Csaba P. (Frontiers in Medicine, 2023)
Background Chronic microinflammation contributes to the progression of chronic kidney disease (CKD). Aspirin (ASA) has been used to treat inflammation for centuries. The effects of long-term low-dose ASA on CKD progression are unclear. Methods We examined the association of long-term use of newly initiated low-dose ASA (50–200 mg/day) with all-cause mortality using Cox proportional hazard models; with cardiovascular/cerebrovascular (CV) mortality and with end stage kidney disease (ESKD) using Fine and Gray competing risk regression models; with progression of CKD defined as patients’ eGFR slopes steeper than −5 mL/min/1.73m2/year using logistic regression models in a nationwide cohort of US Veterans with incident CKD. Among 831,963 patients, we identified 385,457 who either initiated ASA (N = 21,228) within 1 year of CKD diagnosis or never received ASA (N = 364,229). We used propensity score matching to account for differences in key characteristics, yielding 29,480 patients (14,740 in each group). Results In the matched cohort, over a 4.9-year median follow-up period, 11,846 (40.2%) patients (6,017 vs. 5,829 ASA users vs. non-users) died with 25.8% CV deaths, and 934 (3.2%) patients (476 vs. 458) reached ESKD. ASA users had a higher risk of faster decline of kidney functions, i.e., steeper slopes (OR 1.30 [95%CI: 1.18, 1.44], p < 0.01), but did not have apparent benefits on mortality (HR 0.97 [95%CI: 0.94, 1.01], p = 0.17), CV mortality (Sub-Hazard Ratio [SHR]1.06 [95%CI: 0.99–1.14], p = 0.11), or ESKD (SHR1.00 [95%CI: 0.88, 1.13], p = 0.95). Conclusion Chronic low-dose ASA use was associated with faster kidney function deterioration, and no association was observed with mortality or risk of ESKD.